2004
DOI: 10.1111/j.0105-2896.2004.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4‐ and interleukin‐13‐mediated host protection against intestinal nematode parasites

Abstract: Intestinal worm infections characteristically induce T-helper 2 cell (Th2) cytokine production. We reviewed studies performed with mice infected with either of two intestinal nematode parasites, Nippostrongylus brasiliensis or Trichinella spiralis, that evaluate the importance of the Th2 cytokine interleukin-4 (IL-4) and IL-13 in protection against these parasites. These studies demonstrate that while IL-4/IL-13 protect against both parasites by activating signal transducer and activator of transcription 6 (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
393
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 452 publications
(411 citation statements)
references
References 67 publications
15
393
0
3
Order By: Relevance
“…Furthermore, the physiological changes provoked by the worm infection, such as epithelial cell proliferation and goblet cell hyperplasia, were similar in Tregdepleted and control mice. Thus, it seems that H. p. bakeri, which generally leads to chronic infections, tolerates a broad spectrum of Th2-mediated immune and physiological reactions compared with other intestinal nematodes such as Nippostrongylus brasiliensis, T. muris or T. spiralis, which are more efficiently expelled in acute infections [37,38].In conclusion, our data show that Treg are crucial for the control of helminth-induced pathological changes in the intestine and for limiting Th2 responses. Further studies will have to show whether Treg are involved in mediating the general immunosuppression seen in chronic intestinal nematode infections.…”
mentioning
confidence: 70%
See 3 more Smart Citations
“…Furthermore, the physiological changes provoked by the worm infection, such as epithelial cell proliferation and goblet cell hyperplasia, were similar in Tregdepleted and control mice. Thus, it seems that H. p. bakeri, which generally leads to chronic infections, tolerates a broad spectrum of Th2-mediated immune and physiological reactions compared with other intestinal nematodes such as Nippostrongylus brasiliensis, T. muris or T. spiralis, which are more efficiently expelled in acute infections [37,38].In conclusion, our data show that Treg are crucial for the control of helminth-induced pathological changes in the intestine and for limiting Th2 responses. Further studies will have to show whether Treg are involved in mediating the general immunosuppression seen in chronic intestinal nematode infections.…”
mentioning
confidence: 70%
“…The general view suggests that expulsion of adult intestinal nematodes is critically dependent on CD4 1 T cells secreting the Th2 effector cytokines and that these cytokines lead to an inhospitable environment, possibly enabling the expulsion of the parasites in the chronic phase of infection [37,38]. It has also been shown that the application of high doses of recombinant IL-4 abrogates primary infections with H. p. bakeri [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elements of the Th2-type response can control pathologic Th1-type inflammation and also marshal effective helminth resistance; for example, the Th2-type response has a demonstrated role in the expulsion of several intestinal nematode parasites [43,44]. Clearly AAMΦs may contribute to resistance by controlling Th1-type immunity and thereby promoting a potent and polarized Th2-type response.…”
Section: Worm Expulsion and Resistancementioning
confidence: 99%